Jenis Barang Jaminan Gadai Dalam Perspektif Alkitab - Sri Darajad Suaji; Yanto Paulus Hermanto (Tumou Tou, 2022)
The Financial Service Authority Regulation No.31/POJK.05/2016, becomes the legal basis for the establishment of a private pawnshop business, of course this is a new opportunity for people who are business actors and pawnshop service users. One of the important things in the pawnshop business is the type of goods used as collateral, it is not uncommon for borrowers to hand over goods that are actually very important for the borrower's life, which often makes pawnshops not “solve problems without problems” but on the contrary add to problems. With a qualitative approach, using literature sources and the results of previous research, a theological study was conducted to answer the problem of what types of goods are allowed and which are not allowed to be used as collateral for pledges from a biblical perspective. By taking measurements through Christian business ethics, this article tries to answer the problem that the pawnshop business can be used to glorify God's name, namely the profits obtained by the pawnshop entrepreneur and the borrower are carried out by basing themselves on the spirit of helping and loving others, namely the profits of the pawnshop entrepreneur are not obtained through fraud and coercion, while the advantage of the borrower is that it is easy to obtain the loan process and the goods that are guaranteed are not the type of goods that have a direct impact on their lives.